(Not)protest orientation in Ukraine: construction of sociological indices - Бова, А. А. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2018)
The article presents an overview of approaches to the construction of sociological indices of political protest. The first approach involves increasing the power of the scale by assigning respondents’ answers to certain points. Weight coefficients can be determined by the researcher, experts or based on multivariate statistical analysis. The second approach involves constructing an index based on a simple, unweighted sum of the corresponding alternatives. It is established that the readiness for protests can be characterized both in terms of the variety of the choice of protest actions, and in terms of conventional and unconventional forms of political participation. The structure of interrelationships between empirical indicators of protest moods and participation in Euromaidan is considered. The integral indices obtained by recoding the scales characterizing the (non)protest orientations are proposed: the index of orientation toward protest, the index of non-protest orientation, the index of refusal protest/non-protest orientation. For exploratory of the relationships between the four variables the multiple correspondence analysis and Cronbach’s alpha for measurements of the internal consistency of the index scales are used. The empirical base of the research was the data of the study of opinion poll «Ukrainian Society: Monitoring of Social Changes», conducted by the Institute of Sociology NAS of Ukraine in 2014.